Economic feasibility of high Omega-3 soybean oil in mariculture diets: A sustainable replacement for fish oil. Issue 4 (2nd October 2017) - Bairagi, Subir; Perrin, Richard; Fulginiti, Lilyan; Clemente, Thomas; Hungate, Cory; Key, Gavin
ABSTRACT: The growth of global aquaculture has put intense pressure on sources of fish oil and fishmeal for aquafeeds. The nutraceuticals industry has added further pressure on fish oils with high Omega-3 fatty acids. GM soybeans could provide substitutes in high Omega-3 soybean oil (STA oil), as well as soy protein concentrate (SPC). This article examines the technological and economic feasibility of substituting STA oil for one-half the fish oil in the diet of Seriola rivoliana, a species often destined for sushi markets. Previous studies have shown that the substitution results in no change in flesh quality or consumer acceptance. We find that the two feed technologies result in essentially identical growth pattern and feed consumption. Economic feasibility depends upon the price of STA oil being lower than the price of fish oil. Based on our market analysis, we estimate that STA oil will enter the market at a price about two-thirds of the fish oil price. The estimated cost savings at these prices are small, a 2.8% reduction in feed costs and 0.9% reduction in total costs. However, the potential global market for STA oil could be as much as 252 thousand metric tons annually, which would require soybean production equivalent to that from 1.63% of current U.S. soybean area.